Comparative Efficacy Of Cypermethrin, Deltamethrin And Zerokeet Against Brown Dog Ticks - Kumar, P.; Sinha, Sucheta; Sinha, S.R.P.; Gautam, A.K.; Kumari , Sudha; Kumar , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Acaricidal efficacy of two promising pyrethroids, Cypremethrin and Deltamethrin and a herbal preparation Zerokeet in terms of tick mortality and re-infestation period were assessed by spraying against different stages of Rhipicephalus sanguineus on dogs. Cypermethrin was proven to be best followed by Zerokeet and Deltamethrin for tick mortality of all stages and re-infestation period at their recommended dose. Similarly 100 per cent mortality was achieved just within 24 hours on application of 25 per cent enhanced dose of the Cypermethrin and Zerokeet against larva, nymph and adult stages of tick whereas Deltamethrin was 98.6, 95.23 and 90 per cent effective for respective tick stages within 24 hrs and 100 per cent mortality was achieved within 48 hrs on post treatment of enhanced dose of Deltamethrin. Longest reinfestation period was also noted on treatment of Cypermethrin followed by Zerokeet and Deltamethrin . All the drugs were well tolerated without any visual side effect even on enhanced doses.
Keywords: Acaricides; Pyrithroids; Zerokeet